2021
DOI: 10.34184/kssb.2021.9.4.72
|View full text |Cite
|
Sign up to set email alerts
|

Integrated cryoEM imaging center at Seoul National University, Korea

Abstract: The Center for Macromolecular and Cell Imaging (CMCI) is a core facility equipped with multiple cryo-capable electron microscopes including a 200 kV Thermofisher Glacios, 200 kV JEOL JEM2100Plus and 120 kV FEI TECNAI with direct electron detector technologies. The center also has auxiliary equipment for optimal specimen preparation, such as for protein purification, tissue culture, grid preparation and vitrification. The center offers to the scientific community the best practice of cutting-edge cryogenic elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…These findings contributed to understanding the specific contexts that hindered North Korean migrants from participating in community networks. Despite emphasizing inter-organizational cooperation and network establishment [6] for social integration in the community, the specific basis for why interorganizational cooperation was difficult was understood in terms of inter-organizational relations. In other words, it was confirmed that the inequality of mainstream society and minority groups mentioned in [19] was also an obstacle in cooperation between North Korean migrant organizations and South Korean organizations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings contributed to understanding the specific contexts that hindered North Korean migrants from participating in community networks. Despite emphasizing inter-organizational cooperation and network establishment [6] for social integration in the community, the specific basis for why interorganizational cooperation was difficult was understood in terms of inter-organizational relations. In other words, it was confirmed that the inequality of mainstream society and minority groups mentioned in [19] was also an obstacle in cooperation between North Korean migrant organizations and South Korean organizations.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, there were issues about the fragmentation and duplication of services. Regarding this point, [6] argued that NGOs for North Korean migrants should strengthen solidarity and partnership to support North Korean migrants (p. 225) rather than compete with similar programs.…”
Section: The Ngo's General Aims and Activitiesmentioning
confidence: 99%
See 1 more Smart Citation